2014
DOI: 10.1002/asjc.892
|View full text |Cite
|
Sign up to set email alerts
|

H Fault Detection for Two‐Dimensional TS Fuzzy Systems in FM Second Model

Abstract: This paper investigates the H∞ fault detection problem for two-dimensional (2D) Takagi-Sugeno (T-S) fuzzy systems in a Fornasini-Marchesini second (FM II) state-space model. Our aim is to develop fault detection filters for the 2D T-S fuzzy system both in the non-fuzzy case and the fuzzy case. Attention is focused on the design of the above two kinds of fault detection filters, which guarantee the fault detection system to be asymptotically stable and to have a prescribed H∞ performance. Sufficient conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Then, we will prove that the augmented system (12) has an H ∞ disturbance attenuation level 1 under initial zero boundary condition. Define the following performance index:…”
Section: Fault Detection Filter Design Conditionmentioning
confidence: 98%
See 4 more Smart Citations
“…Then, we will prove that the augmented system (12) has an H ∞ disturbance attenuation level 1 under initial zero boundary condition. Define the following performance index:…”
Section: Fault Detection Filter Design Conditionmentioning
confidence: 98%
“…It is obvious that inequality (25) is equivalent to condition (13). Based on Definition 2, it is concluded that the augmented system (12) has an H ∞ disturbance attenuation level 1 . The proof is completed.…”
Section: Fault Detection Filter Design Conditionmentioning
confidence: 99%
See 3 more Smart Citations